DETERMINANTS OF UNMET NEEDS IN MARRIED WOMEN IN INDONESIA (INDONESIAN DHS ANALYSIS 2017) - Bethania Amruh Nisak (Universitas Airlangga, 2021)
The incidence of unmet needs in Indonesia is still high, around 10.6 percent. For every 36 million couples of childbearing age, there are 4 million couples who experience unmet needs. The high number of unmet needs will trigger various effects on women of childbearing age. One of the impacts is unwanted pregnancy. This unwanted pregnancy can be a factor in morbidity and mortality in the mother, increasing maternal mortality if not addressed promptly. This study is an observational non-reactive study. This study aimed to determine the factors related to the unmet need for family planning in married women. The study subjects were 29,189 married women aged 15-49 years old (women of childbearing age). The data source comes from the Indonesian Demographic and Health Survey (IDHS) in 2017. Further analysis was carried out using the chi-square test and multiple logistic regression. The results show that the factors affecting the unmet need for family planning in women are the age of women, the number of children who are still alive, family planning discussions between spouses or husband and wife, education level, employment status, knowledge related to methods, and history of family planning use. The variable of family planning usage history is the most influential factor in the unmet need for family planning in pregnant women. Women who have never done birth control have a high risk of unmet need—women's knowledge about contraceptive methods related to the contraceptive method and the history of using family planning (p-value <0.05). The variable of family planning usage history is the most influential factor in the unmet need for family planning in pregnant women. Women who have never done birth control have a high risk of unmet need—knowledge related to family planning methods and history (p-value <0.05). The variable of family planning usage history is the most influential factor in the unmet need for family planning in pregnant women. Women who have never done birth control have a high risk of unmet need.